Fear of Success as a Function of Psychological Androgynous Tendencies among Women in Managerial Positions - Fagbemi, Funmi Mowaiye - (NIU Journal of Humanities, 2018)
The dearth of studies on fear of success syndrome and psychological androgyny in Nigeria has earlier been reported (Mowaiye-Fagbemi, 2000). Also noted however, are research efforts in this area. Fear of success has been highly linked to psychological androgyny. In an earlier research report, Mowaiye-Fagbemi, (2000) noted that there was a significant relationship to be found between fear of success and sex role orientation. Subjects in the study who were less disposed to fear of success were also rigid as regards sex role orientation among other reports. However, the subjects were students in tertiary institutions in the Nigeria. The present research study was aimed at espousing more on the variables under study. It was further aimed as a follow-up to the earlier research reported by Mowaiye-Fagbemi, (2000). In the  present study , subjects were  women in the higher echelons of educational management, this was aimed at finding out if indeed the two syndromes under study holds sway for women in such higher echelons of management and if there could be a significant relationship among the variable among the women.